Mathematical Simulation of Vibropercussion Units where Solid Bodies are Connected in a Chain Ramificated Way - Нісонський, Володимир Павлович; Шопа, Василь Михайлович; Герега, Ігор Іванович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
A mathematical simulation of the dynamic work regime of vibropercussion units where solid bodies are connected in a chain ramificated way is presented in this paper. The variable mass of technological loading and contact of working surfaces is taken into consideration. The system of equations is given in a matrix way. The dynamic scheme of vibrograte model 31327 is considered.